Influence of Pseudomonas autoinducer N-3-oxododecanoyl homoserine lactone on human corneal epithelial cells. Issue 4 (February 2021) - Hu, Renjian; Yuan, Kelan; Zhou, Jie; Zhang, Yue; Zheng, Jiao; Zhao, Yingying; Huang, Xiaodan; Jin, Xiuming
The quorum-sensing (QS) signaling-dependent extracellular virulence factors of Pseudomonas aeruginosa can cause infections such as P. aeruginosa keratitis. P. aeruginosa communicates by secreting and sensing small chemical molecules called autoinducers in QS system. The key QS signal molecule, N -3-oxododecanoyl-homoserine lactone (3OC12HSL), can affect the behavior of host cells and initiate immune response. In this report we investigated the influence of 3OC12HSL on human corneal epithelial cells (HCECs) and the mechanisms of 3OC12HSL on activated toll-like receptor 2 (TLR2)-dependent interleukin-8 (IL-8) secretion in HCECs. Cells were cultured under different concentrations of 3OC12HSL. Cell viability was assessed using Crystal violet staining and the cell counting kit-8 assay. We demonstrated the administration of 3OC12HSL decreased HCEC viability and survival in a concentration- and time-dependent manner. At high concentrations, 3OC12HSL rapidly promoted a time-dependent increase in the expressions of TLR2 and TLR4. It was found that the nuclear translocation and expression of nuclear factor-κB (NF-κB) were also increased in response to 3OC12HSL treatment. The significantly elevated expressions of TLR2, TLR4, and NF-κB, encouraged us to further test their mechanisms that cause inflammatory response. Among the inflammatory factors examined (IL-6, IL-8, IL-10, and TNF-α), we found that IL-8 was significantly increased after treatment with 3OC12HSL and its expression was inhibited when TLR2 was specifically blocked or silenced. These results indicated that the QS signaling molecule 3OC12HSL could be recognized by the host innate immune system in HCECs. This recognition then triggered an immune inflammatory response involving the activation of TLR2 and an increase in expression of IL-8. This crosstalk between 3OC12HSL and host immunity in HCECs contributes to the development and progression of P. aeruginosa keratitis.